2017
DOI: 10.2174/1874285801711010142
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Inhibitory Concentrations of Rifampicin Strongly Stimulated Biofilm Production in S. aureus

Abstract: Background and Objectives: Staphylococcus aureus is an important pathogen and a frequent cause of infections associated with biofilm production in implantable medical devices. Biofilm production can be induced by sub-inhibitory concentrations (sub-MICs) of certain antibiotics, but few studies have researched this occurrence in S. aureus. In this study, we investigated the effect of sub-MICs of rifampicin and minocycline on biofilm production by five clinical and five non-clinical S. aureus isolates.Methods:Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
1
14
1
Order By: Relevance
“…Long-term RIF monotherapy at sub-inhibitory concentrations (RIF MIC in combination ) did not prevent bacterial biofilm formation. Moreover, in contrast with earlier findings against staphylococcal biofilms [38], RIF did not seem to stimulate biofilm production.…”
Section: Macrolides and Rifampicin Versus Biofilm: A Controversial Issuecontrasting
confidence: 99%
“…Long-term RIF monotherapy at sub-inhibitory concentrations (RIF MIC in combination ) did not prevent bacterial biofilm formation. Moreover, in contrast with earlier findings against staphylococcal biofilms [38], RIF did not seem to stimulate biofilm production.…”
Section: Macrolides and Rifampicin Versus Biofilm: A Controversial Issuecontrasting
confidence: 99%
“… 57 For example, Lima-e-Silva et al reported that in sub-lethal doses (MIC/2 and MIC/4), rifampin strongly stimulated biofilm-formation (when measured by the CRA plate and CV microtiter plate assay), in contrast to minocycline, which did not have such inducing effects. 58 The effects of low antibiotic doses on the biofilm-forming capacity are thought to occur by differential expression of genes of interest due to the noxious agents. 59 The literature has shown that sub-MIC concentrations of tetracycline, quinupristin and dalfopristin were presented as strong inducers, while erythromycin was noted as a weak inducer of ica -gene expression.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…As already known, most antibiotics treatments are not effective against S. aureus biofilms. Worse, several studies have shown that antibiotics treatments can induce biofilm formation [ 61 , 62 ]. For now, rifampicin (rifampin) is the most efficient antibiotic against S. aureus biofilms; presents a good penetration into bone tissues; and shows good efficacy in vitro, in vivo, and in clinical PJIs.…”
Section: Antibiotic Failure In Pji Due To S Aureus mentioning
confidence: 99%